2015
DOI: 10.7554/elife.11396
|View full text |Cite
|
Sign up to set email alerts
|

An essential role of acetylcholine-glutamate synergy at habenular synapses in nicotine dependence

Abstract: A great deal of interest has been focused recently on the habenula and its critical role in aversion, negative-reward and drug dependence. Using a conditional mouse model of the ACh-synthesizing enzyme choline acetyltransferase (Chat), we report that local elimination of acetylcholine (ACh) in medial habenula (MHb) neurons alters glutamate corelease and presynaptic facilitation. Electron microscopy and immuno-isolation analyses revealed colocalization of ACh and glutamate vesicular transporters in synaptic ves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
92
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(105 citation statements)
references
References 101 publications
(158 reference statements)
9
92
0
4
Order By: Relevance
“…We have previously observed that the vesicular coentry of glutamate through VGLUT can increase the driving force for VMAT2-mediated exchange in both mice and flies (6,54). This mechanism can increase the quantal content of DA and other cationic transmitters (6,(55)(56)(57)(58), but could also help sequester toxic VMAT2 substrates, such as 6-OHDA or 1-methyl-4-phenylpyridinium (MPP + ), away from sensitive cellular compartments or processes. Thus, increased resistance of VGLUT2-expressing DA neurons to neurotoxins is likely to explain at least some of the effects we observe following DA neuron injury with striatal 6-OHDA or systemic MPTP.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously observed that the vesicular coentry of glutamate through VGLUT can increase the driving force for VMAT2-mediated exchange in both mice and flies (6,54). This mechanism can increase the quantal content of DA and other cationic transmitters (6,(55)(56)(57)(58), but could also help sequester toxic VMAT2 substrates, such as 6-OHDA or 1-methyl-4-phenylpyridinium (MPP + ), away from sensitive cellular compartments or processes. Thus, increased resistance of VGLUT2-expressing DA neurons to neurotoxins is likely to explain at least some of the effects we observe following DA neuron injury with striatal 6-OHDA or systemic MPTP.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some of our PHA‐L or CTb injections were small enough to permit well‐founded conclusions about the topography of some IP inputs and outputs. For example, MHb projections to the IP have been investigated in great detail using conventional tracing techniques (Contestabile & Flumerfelt, ; Kim, ), immunohistochemical studies (Contestabile et al, ), as well as several distinct approaches in genetically modified mice (e.g., Broms, Antolin‐Fontes, Tingström, & Ibañez‐Tallon, ; Frahm et al, ; Hsu et al, ; Quina et al, ; Ren et al, ; Shih et al, ). Altogether, these studies highlighted that, whereas the IPL and dorsal cap of the IP are mainly innervated by glutamate/substance P axons arising from the MHbD, all remainder IP subnuclei are abundantly innervated by glutamate/acetylcholine axons emerging from MHbV (for a recent review, see Antolin‐Fontes et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…There is now broad consensus that the MHb‐IP axis plays a major role in nicotine mediated reward and withdrawal behaviors (for reviews, see Antolin‐Fontes et al, ; Fowler & Kenny, ; Jackson, Muldoon, De Biasi, & Damaj, ). Thus, distinct nAChRs have been shown to mediate key responses to nicotine through mechanisms including presynaptic facilitation of glutamate release by MHb axons in the IP (Frahm et al, ), and the regulation of pacemaker activity of cholinergic neurons in the MHbV (Görlich et al, ), which remarkably are able to co‐release acetylcholine and glutamate in the IP via different transmission modes (Ren et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Together, these data indicate that, under conditions of nicotine abstinence, the IPN is activated through mHb signaling (most notably via excitatory glutamatergic input), triggering an anxiety-like response. The distinct regulatory pathways of IPN glutamatergic signaling may pass through a mechanism whereby ACh is able to control the release frequency of Glu at habenular synapses and hence, the behavioral responses to nicotine [47]. …”
Section: The Mhb-ipn Axis In Nicotine Withdrawal-induced Negative Emomentioning
confidence: 99%